KEUNGGULAN KOMPETITIF KOPI ARABIKA TERINDIKASI GEOGRAFIS CV BALI BEANS, DESA BELOK SIDAN, KABUPATEN BADUNG - I Komang Putra Handika; I Made Tamba; Luh Putu Kirana Pratiwi, (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2024)
Arabica coffee (coffea arabica) is one of these commodities, among others, as a source for plantations which has an important role in earning foreign exchange, providing employment opportunities, in the Indonesian economy. Role and as a source of income for coffee planters and other economic actors involved in cultivation, processing, marketing, as well as in the upstream and downstream chains. The development of smallholder coffee plantation areas in Indonesia is currently quite rapid, so it needs to be supported by the readiness of processing facilities and methods that are suitable for farmers' conditions so that they are able to produce coffee beans of the quality required by the Indonesian National Standards. The existence of a definite quality guarantee, followed by availability in sufficient quantities and timely and sustainable supply are some of the prerequisites needed so that people's coffee beans can be marketed at a reasonable price level. To fulfill the prerequisites above, people's coffee processing must be carried out at the right time, in the right way and in the right quantity. Harvested coffee fruit, like other agricultural products, needs to be immediately processed into a stable final product so that it is safe to store for a certain period of time. The quality criteria for clean beans as well as aspects of uniformity and consistency are determined by the treatment at each stage of the production process.